2013
DOI: 10.1155/2013/420164
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Ability of Adult Stem Cell in Skeletal Muscle: An Effective and Replenishable Resource to the Establishment of Pluripotent Stem Cells

Abstract: Adult stem cells play an essential role in mammalian organ maintenance and repair throughout adulthood since they ensure that organs retain their ability to regenerate. The choice of cell fate by adult stem cells for cellular proliferation, self-renewal, and differentiation into multiple lineages is critically important for the homeostasis and biological function of individual organs. Responses of stem cells to stress, injury, or environmental change are precisely regulated by intercellular and intracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 186 publications
0
21
0
Order By: Relevance
“…The Notch signaling participates in the satellite cell quiescence 26. Inhibition of the Notch signaling in satellite cells, as well as the deficiency of Ten‐4 as shown in this study, forces to exit the quiescent state 13, 14, 15.…”
Section: Discussionmentioning
confidence: 60%
“…The Notch signaling participates in the satellite cell quiescence 26. Inhibition of the Notch signaling in satellite cells, as well as the deficiency of Ten‐4 as shown in this study, forces to exit the quiescent state 13, 14, 15.…”
Section: Discussionmentioning
confidence: 60%
“…Wnt-mediated expression of myogenic genes in satellite cells caused their conversion from the quiescent state into the activated state in both adult and aged mice. Wnt signaling plays an important role in embryonic muscle development (7,34). The neural tube expresses Wnt1, which activates the Myf5 gene, whereas the dorsal ectoderm expresses Wnt7a, which promotes MyoD expression (46).…”
Section: Discussionmentioning
confidence: 99%
“…2F). These data suggested that the relatively high levels of up-regulation of the Voluntary Wheel Running Activated Canonical Wnt/␤-Catenin Signaling-To examine the molecular mechanisms underlying satellite cell activation after running, we focused on the Notch and Wnt signaling pathways, which regulate satellite cell self-renewal and myogenesis at the developmental embryonic stage (34). The expression of Delta ligand 4 (DLL4) and HeyL, which are the ligand and target gene, respectively, in Notch signaling, tended to decrease slightly after exercise in both the adult and aged groups (Fig.…”
Section: Voluntary Wheel Running Activated Satellite Cells and Prolifmentioning
confidence: 99%
“…; Fujimaki et al . ). It has been envisaged that age‐related activation of Wnt/β‐catenin signal during myogenic differentiation results in delayed or suppressed myogenic differentiation and thereby impairing the function of the skeletal muscles (Brack et al .…”
Section: Discussionmentioning
confidence: 97%